Intelligent Vascularized 3D/4D/5D/6D-Printed Tissue Scaffolds - Han, Xiaoyu; Saiding, Qimanguli; Cai, Xiaolu; Xiao, Yi; Wang, Peng; Cai, Zhengwei; Gong, Xuan; Gong, Weiming; Zhang, Xingcai; Cui, Wenguo (Nano-Micro Letters, 2023)
Blood vessels are essential for nutrient and oxygen delivery and waste removal. Scaffold-repairing materials with functional vascular networks are widely used in bone tissue engineering. Additive manufacturing is a manufacturing technology that creates three-dimensional solids by stacking substances layer by layer, mainly including but not limited to 3D printing, but also 4D printing, 5D printing and 6D printing. It can be effectively combined with vascularization to meet the needs of vascularized tissue scaffolds by precisely tuning the mechanical structure and biological properties of smart vascular scaffolds. Herein, the development of neovascularization to vascularization to bone tissue engineering is systematically discussed in terms of the importance of vascularization to the tissue. Additionally, the research progress and future prospects of vascularized 3D printed scaffold materials are highlighted and presented in four categories: functional vascularized 3D printed scaffolds, cell-based vascularized 3D printed scaffolds, vascularized 3D printed scaffolds loaded with specific carriers and bionic vascularized 3D printed scaffolds. Finally, a brief review of vascularized additive manufacturing-tissue scaffolds in related tissues such as the vascular tissue engineering, cardiovascular system, skeletal muscle, soft tissue and a discussion of the challenges and development efforts leading to significant advances in intelligent vascularized tissue regeneration is presented. Highlights: 1 Comprehensive and systematic discussion of vascularized additive manufacturing scaffolds for bone tissue repair is provided. 2 The development mechanism of blood vessels and the relationship between bone tissue engineering and blood vessels are discussed. 3 Vascularized additively manufactured scaffolds in tissue repair are discussed in terms of issues, opportunities, and challenges. 4 Intelligent vascularized 3D/4D/5D/6D-printed tissue scaffolds are discussed.